2020
DOI: 10.1111/cyt.12812
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative image analysis for CD8 score in lung small biopsies and cytology cell‐blocks

Abstract: Introduction Immunotherapy has shown promising results in non‐small cell lung cancer (NSCLC), for which tumour‐infiltrating cytotoxic (CD8+) T cells play a critical role. We investigated the utility of image analysis (IA) to quantify CD8+ T cells in a series of matched small biopsies and resections of NSCLC. Methods CD8 immunohistochemistry was performed on cell‐blocks (CB), core needle biopsies (CNB) and corresponding resections from primary NSCLCs. Slides were digitised using an Aperio AT2 scanner (Leica) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Many studies have shown that CD8 + in ltrated in tumors plays an important role in anti-tumor immune response. The in ltration of CD8 + high-expressing T cells in tumors helps to improve the clinical outcome of cancers including NSCLC [23][24]. NK cells constitute the rst line of defense against microbial infections and cancer development.…”
Section: Effects Two Anesthetics On Hemodynamics During Perioperative Periodmentioning
confidence: 99%
“…Many studies have shown that CD8 + in ltrated in tumors plays an important role in anti-tumor immune response. The in ltration of CD8 + high-expressing T cells in tumors helps to improve the clinical outcome of cancers including NSCLC [23][24]. NK cells constitute the rst line of defense against microbial infections and cancer development.…”
Section: Effects Two Anesthetics On Hemodynamics During Perioperative Periodmentioning
confidence: 99%
“…How the assessment of LAG-3 and other immunoregulators may vary on cytologic specimens remains largely unknown, whereas the use of cytology smears or cell blocks for the assessment of immune cell markers that are more abundant in tumor-associated stroma24 may not seem appropriate. Furthermore, although currently most of the clinical assessment of PD-L1 expression relies on a manual semiquantitative approach, computer-assisted quantitative analysis of PD-L1 expression and CD8 + tumor-infiltrating lymphocytes has been reported,37,38 and this has included the use of cytology specimens 39. Nevertheless, because of the increasing use of ICIs in oncology, for diagnostic surgical pathology and cytopathology, further research and clinical implementation of additional predictive biomarkers, including LAG-3, are yet to come.…”
mentioning
confidence: 99%